The gut microbiome in deformed wing virus (DWV)-uninfected and -infected Apis cerana honeybees suggests the role of gut microbiota in combating viral infections - Dong, Van Quyen; Pham, Thi Lanh (Academia Journal of Biology, 2024)
Honeybees harbor a distinct core microbiota that plays a crucial role in stress tolerance and disease resistance. However, infections can significantly alter the composition and diversity of their gut microbiota, impacting overall bee health. This study investigates the effects of Deformed Wing Virus (DWV) infection on the gut microbiota of Apis cerana honeybee. The samples were collected from six colonies in Hanoi, Vietnam, and analyzed using high-throughput sequencing of the 16S rRNA gene. Our results show that while the overall diversity of gut microbiota in DWV-infected and uninfected bees did not significantly differ, notable changes were observed in the relative abundances of specific bacterial taxa. In DWV-infected bees, the relative abundance of Proteobacteria significantly decreased, whereas Firmicutes increased compared to uninfected bees. At the genus level, a significant decrease in Gilliamella and an increase in Lactobacillus were observed in infected bees. Functional gene predictions indicated that pathways related to carbohydrate, fatty acid, and lipid metabolism, as well as the biosynthesis of cofactors, vitamins, and amino acids, were upregulated in DWV-infected bees. These findings highlight the impact of DWV infection on the gut microbiota of A. cerana and suggest potential avenues for using probiotics to restore gut microbial balance and improve honeybee health. This research provides a foundation for developing strategies to enhance the resilience of honeybee colonies against viral infections.